INTERMEDIAL CODE OF THE PARISHISTICAL NOVEL «LOVERS OF JUSTICE» BY YURI ANDRUKHOVYCH - Yurchuk, О. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the intermediate code of Yuri Andrukhovych's paradigmatic novel «Lovers of Justice». The features of the complexity of literary and cinematic techniques are described. Particular attention is paid to the following elements of the architectonics of the novel: recombinated composition, visual graphic segmentation, offscreen author's voice, the limited dialogue space, interframe filling. It is demonstrated that inter-artistic interaction allows the artist to create a special space for self-presentation, as well as create an excellent (more relevant) the dimension of the existence of literary text / literary form.